Iluzija zavesti - Lipuš, Alen (visokošolska dela, 2020)
The dissertation first presents a central problem in contemporary philosophy of mind, i.e. the problem of phenomenal consciousness, and highlights that, due to the ambiguity of the terms used, the problem is difficult to define. Then it presents the key concepts that constitute the problem of consciousness and provides an analysis of the contemporary dialectical situation regarding the problem of consciousness, followed by a discussion of traditional solutions to the problem, which are presented as insufficient. Afterwards, the focus is on the meta-approach, for which a critical investigation of the underlying assumptions is characteristic. A meta-analysis of the problem of consciousness is the best approach for understanding the soundness of the problem of phenomenal consciousness and for evaluating individual positions that have so far been formed as reactions to the problem. In order for the question of the placement of consciousness in the world to make sense, it has to be presupposed that consciousness is stuff of the same type as other extended things; it also has to be presupposed that consciousness is exactly as it seems to us, for it is precisely the appearance of consciousness that makes it difficult to place in the world; and it has to be presupposes that there is no distinction between appearance and reality when it comes to consciousness. In the meta-analysis, the dissertation articulates these presuppositions and evaluates the consequences of accepting or denying them. The dissertation shows that some presuppositions (e.g. the presupposition of identity of appearance and reality of consciousness) are such that accepting them uncritically results in a "theoretical tax" that is too high, and thus we must not perceive them as axiomatic, self-evident starting points in research. The dissertation also justifies illusionism as one of the meta-approaches to solving the problem of phenomenal consciousness, and suggests that it is the best strategy for physicists, i.e. adherents of the view that mental states are essentially physical. The dissertation then presents and treats illusionism as a physicalist theory of consciousness. It critically examines the process of establishing illusionism and presents the reasoning that usually leads to it: it describes and critically evaluates the original establishing conditions for illusionism and shows that, in the current literature, illusionism is established in a problematic way and as is thus an incoherent position. The dissertation further considers various critiques of illusionism, addresses them, and presents a new problem, which suggests that illusionism is not established coherently. Finally, the theoretical advantages of successfully solving this new problem are described - most notably, by successfully solving the new problem illusionism can become a coherent theory ..., which can also help in defending illusionism against other, already established critiques.
Keywords: consciousness; disertacije; dissertations; hard problem of consciousness; illusionism; iluzionizem; phenomenality; pojavnost; qualia; takšnosti; težek problem zavesti; zavest